Ecofeminism Among Women Farmers in Pakel Village, Banyuwangi: An Ethnographic Study Amidst Land Conflicts - Sari, Fitria Novita; Azhari, R. Farhan Fadhila (Biokultur, 2025)
In conflicts and struggles, women are both actively involved and affected, as discussed in various studies. However,research on the lives of women farmers in land conflicts in Pakel village, Banyuwangi Regency, is still limited. Thisstudy aims to describe the lives of women farmers in land conflicts that occur in Pakel village, BanyuwangiRegency. Pakel Village was chosen as the research location because the women had been abandoned by the men toavoid police arrest during a land conflict, leaving them to survive on their own. This qualitative research approachuses ethnographic methods with ecofeminism theory from Vandana Shiva. Primary data was collected throughparticipant observation, informal interviews, and in-depth interviews. The technique of determining informants inthis study used snowball sampling with a total of five female informants to be interviewed in depth. The resultsshowed that women farmers in Pakel village, Banyuwangi Regency, played an active role in the struggle. From theirdual roles as heads of households and housewives in the pre-land reclamation period to their active participation androles in various aspects of their daily activities after the land reclamation—such as farming, cooking, caring forchildren and/or grandchildren, istighosah, mediating conflicts, participating in night patrols, and fighting back. Theviolence in this land conflict also had a traumatic impact on one of the women farmers, so psychological serviceswere provided. Further research is needed to better understand the role of women in land conflicts in Pakel village,Banyuwangi Regency, with different themes and from various disciplines.